2016
DOI: 10.2214/ajr.16.16307
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Split Renal Function With 99mTc-DMSA SPECT: Comparison Between 3D Volumetric Assessment and 2D Coronal Projection Imaging

Abstract: OBJECTIVE Split renal function (SRF) can be estimated with 99mTc-labeled dimercaptosuccinic acid (DMSA) SPECT cortical renal scintigraphy on either 2D projected images or 3D images. The purpose of this study was to determine whether there is a significant difference between SRF values calculated with the 2D method and those calculated with the 3D method. MATERIALS AND METHODS This retrospective study was performed with 99mTc-DMSA SPECT images of 316 patients (age range, 1–26 years). All images were reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…If pinhole views are required, the guidelines advocate 100,000 -150,000 counts for better detection of small cortical defects. In the majority of cases high-quality static planar images are sufficient for an accurate diagnostic assessment, but a SPECT acquisition, with the possible addition of a low dose CT (where such a scanner is available), can be useful in complex cases, such as crossed-fused renal ectopia and complex renal stones (22,23). Recent studies have suggested Tc-99m-DMSA scintigraphy for predicting dilating vesicoureteral reflux (VUR) in young children with febrile urinary tract infection but so far only limited (and sometimes conflicting) data is available in the literature (24)(25)(26)(27)(28)(29).…”
Section: Static Cortical Renal Scintigraphymentioning
confidence: 99%
“…If pinhole views are required, the guidelines advocate 100,000 -150,000 counts for better detection of small cortical defects. In the majority of cases high-quality static planar images are sufficient for an accurate diagnostic assessment, but a SPECT acquisition, with the possible addition of a low dose CT (where such a scanner is available), can be useful in complex cases, such as crossed-fused renal ectopia and complex renal stones (22,23). Recent studies have suggested Tc-99m-DMSA scintigraphy for predicting dilating vesicoureteral reflux (VUR) in young children with febrile urinary tract infection but so far only limited (and sometimes conflicting) data is available in the literature (24)(25)(26)(27)(28)(29).…”
Section: Static Cortical Renal Scintigraphymentioning
confidence: 99%
“…Absolute renal uptake (ARU %) is a quantifiable parameter to assess the absolute kidney function for each kidney independently. Multiple previous studies have discussed various methods for calculation of ARU (%) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We used posterior view for image acquisition which is probably a practical method for ARU (%) quantification and could be easily incorporated in the routine processing of daily clinical renal studies as acquired by H.I abdelkader et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies exist in ARU (%) values due to various quantitative methods used and standardization of normal ARU (%) values is probably required at different centers [1]. SRF, differential renal function, or relative kidney function are commonly expressed as a percent of total renal function [2]. Information about SRF is very important in patients with unilateral renal disorders and is used to understand and predict sufficient postoperative renal function, otherwise, other options such as renal replacement therapy must be considered [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of SRF, scintigraphic methods are used such as technetium‐99m‐mercaptoacetyltriglycine ( 99m Tc‐MAG3), 99m Tc‐DTPA, technetium‐99m‐dimercaptosuccinic acid ( 99m Tc)‐DMSA and chromium‐51 ethylenediamine tetraacetic acid ( 51 Cr‐EDTA) and so forth. (Cao et al, 2016; Chroustová et al, 2016; Gardan et al, 2018; Miyazaki et al, 2010; Ritchie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%